Prospective clinical assessment of tibial tuberosity advancement for the treatment of cranial cruciate ligament rupture in dogs - Barros, Luciano Pereira de; Rios Ribeiro, Laura Raquel; Camonda Pereira, Cordeiro de Pina; Maschio Ferreira, Fernando Lucas; Andrade Moutinho da Conceicao, Maria Eduarda Bastos [UNESP]; Gosuen Goncalves Dias, Luis Gustavo [UNESP] (Acta Cirurgica Brasileira, 2018)
Purpose: To evaluate clinically dogs that underwent tibial tuberosity advancement (TTA) six months previously. Methods: Dogs of various breeds, gender, weight, and age that had CCL rupture and underwent TTA for treatment were included in this study. Parapatellar arthrotomy was performed in all patients to assess the joint for a ruptured ligament and meniscal injury before the TTA. The appropriate cage for the TTA was chosen with planning surgery. The surgical procedure was performed according to the literature, using a modified Maquet technique. Six months after surgery, lameness during walking; muscular atrophy; crepitation, cranial drawer and tibial compression tests and quality of life based on owner's evaluation were assessed. Results: Postoperative complications were observed in only one knee (4.76%), with a surgical site seroma. The mean lameness score at walking was 0.29 (+/- 0.64). The mean score regarding muscular atrophy was 0.95 (+/- 1.56). The mean score of the cranial drawer test, in a range from 0 to 5, was 1.52 (+/- 1.54). The owners rated the dog's quality of life as excellent in 44%, good in 30%, and moderate in 17%. Conclusion: This clinical study supports the affirmation that patients who undergo TTA for treatment of CCL rupture have an acceptable response.
Keywords: Orthopedics; Osteotomy; Veterinary; Dogs